OTOMASISASI SISTEM PENCATATAN KWH METER DAN PENGAWASAN TERHADAP PENCURIAN DAYA PLN DENGAN TEKNOLOGI GSM - Rahmad Sadli; Fitriady (J-Innovation, 2015)
Electrical energy is one of the very important resources in a modern society. Therefore, PT PLN(Persero), as a provider ofelectricity, musthave a high integrityin serving ofelectrical energy for the society. One of the effective ways to improve the quality of service is done by recording KWH meter remotely usingGSM technology. This system consistsof clients (customers) andserver(PLN) side. The usaged of the KWH meter is read by the microcontroller system on the KWH meter side. Then, these data are transmitted to PLN server by using the SMS feature that is available in the GSM technolgy. The KWH meter is also equipped with theft of power monitoring system by adding anelectronic seal sensor on the KWH meterbox. If these alisre moved, the system will immediately send a message to PLN server tells that the custumer has already broken the seal, and the suplay of power to the custumeris cut automatically